Remarks on "Analysis of one popular group signature scheme" in Asiacrypt 2006. (1st September 2009) - Ateniese, Giuseppe; Camenisch, Jan; Joye, Marc; Tsudik, Gene
At Asiacrypt 2006, Cao presented a putative framing 'attack' against the ACJT group signature scheme by Ateniese et al. This paper shows that the attack framework considered by Cao is invalid. As we clearly illustrate, there is no security weakness in the ACJT group signature scheme as long as all the detailed specifications of the original paper are being followed.